PKM pelatihan membuat jamban sederhana model sumuran di Kabupaten Sidenreng Rappang - Heru Winarno; Bakhrani A. Rauf; Panennungi T (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
This social work aimed to improve: (1) partner’s knowledge well model-plain toilet (2) partner’s skill to well model-plain toilet and (3) the skill to construct well model-plain toilet. The methods that used of this social work were: (1) to improve the knowledge of people about the well model-plain toilet then the discourse, interactive and discussion method are conducted, (2) to improve their skill to design the well model-plain toilet then methods discourse, interactive, discussion, and demonstration are conducted and (3) to improve the skill to make the well model-plain toilet then discourse, interactive, discussion, demonstration, and training methods are conducted. The results of social work, (1) the people was highly motivated to follow these activities; (2) the material of workshop was responded by people because of well model-plain toilet was easy to be made and the compound could be gained in workshop location; (3) well model-plain toilet could be accepted, understood, and followed by people technically; (4) the people were ready to make their own well model-plain toilet construction in their house and inform to others.